Implementing antibody-drug conjugates (ADCs) in HER2-positive breast cancer: state of the art and future directions - Emanuela Ferraro; Joshua Z. Drago; Shanu Modi (Breast Cancer Research, 2021)
Abstract The development of anti-HER2 agents has been one of the most meaningful advancements in the management of metastatic breast cancer, significantly improving survival outcomes. Despite the efficacy of anti-HER2 monoclonal antibodies, concurrent chemotherapy is still needed to maximize response. Antibody-drug conjugates (ADCs) are a class of therapeutics that combines an antigen-specific antibody backbone with a potent cytotoxic payload, resulting in an improved therapeutic index. Two anti-HER2 ADCs have been approved by the FDA with different indications in HER2-positive breast cancer. Ado-trastuzumab emtansine (T-DM1) was the first-in-class HER2-targeting ADC, initially approved in 2013 for metastatic patients who previously received trastuzumab and a taxane, and the label was expanded in 2019 to include adjuvant treatment of high-risk patients with residual disease after neoadjuvant taxane and trastuzumab-based therapy. In 2020, trastuzumab deruxtecan (T-DXd) was the second approved ADC for patients who had received at least 2 lines of anti-HER2-based therapy in the metastatic setting. The success of these two agents has transformed the treatment of HER2-positive breast cancer and has re-energized the field of ADC development. Given their advanced pharmaceutical properties, next-generation HER2-targeted ADCs have the potential to be active beyond traditional HER2-positive breast cancer and may be effective in cells with low expression of HER2 or ERBB2 mutations, opening a spectrum of new possible clinical applications. Ongoing challenges include improving target-specificity, optimizing the toxicity profile, and identifying biomarkers for patient selection. The aim of this review is to summarize the principal molecular, clinical, and safety characteristics of approved and experimental anti-HER2 ADCs, contextualizing the current and future landscape of drug development.